Subsurface Tectonic Inferences of the Adamawa Region of Cameroon from EMAG2 Magnetic Data - Kasi Njeudjang; Justine Yandjimain; Apollinaire Bouba; Boris Merlain Djousse Kanouo; William Assatse Teikeu; Noël Djongyang; Théophile Ndougsa-Mbarga (International Journal of Geophysics)
The study area includes an area between 6° to 8°N and 11° to 15°E. Geologically, it belongs to Precambrian basement (granites, gneisses), Proterozoic, and Archean (volcanic) series, showing the main heat sources of Cameroon. The purpose of this study deals to analyze and interpret the EMAG2 magnetic data in the Adamawa area using various advanced processing techniques. Thus, the mapping and depth estimation of underground structures are realized. The analysis of aeromagnetic map of the reduction to equator (RTE) in Adamawa area reveals rapidly evolving subsurface geological presented its lithological and structural. In the same, the power spectrum-processing tool clearly emphasizes shallow and deep underground heat sources. Two magnetic source location methods (source parameter imaging and analytical signal) are used to characterize of the source. The estimated magnetic source depths from source parameter imaging (SPI) are between 0.3 km and 22 km. The analytical signal ranges from 0.2 km to 31 km. In addition, the comparative study of 2D magnetic modelling showed that the basement is affected by the faults in the main directions of N-S, NE-SW, NW-SE, and WNW-ESE. The resulting structural map based on the tectonic map of Adamawa magnetic basement is a document that can simplify future hydrological and geothermal exploration.